LEARNING DURING THE COVID-19 PANDEMIC: OPTIMISM OF ELEMENTARY SCHOOL TEACHERS IN IMPLEMENTING ONLINE LEARNING - Megah Syifa Rinjani (Universitas Pendidikan Indonesia, 2023)
Changes in education sector due to the Covid-19 pandemic resulting in changes to teaching and learning activities making teachers have to adapt to online learning implementation. Optimism is an internal factor that is relevant to predict the teachers’ readiness to face the future, given the meaning namely positive belief that individuals have in viewing their future. A qualitative method was carried out on seven elementary school teachers to find the overview of their optimism on teaching during Covid-19 pandemic. It was found that teachers did not feel optimistic at the beginning of the pandemic situation but begin to show optimism after one semester of teaching online. After conducting thematic analysis, we found that teachers show optimism in the form of three dimension of optimism with the most dominant behavior appeared in the form of personalization dimension. It is concluded that elementary school teachers have better chances to be optimist during teaching in the Covid-19 pandemic time, which implies that they will be motivated to try to overcome the difficulties they encounter.